2018
DOI: 10.1016/j.ejpb.2018.05.031
|View full text |Cite
|
Sign up to set email alerts
|

Development of PLGA nanoparticle loaded dissolving microneedles and comparison with hollow microneedles in intradermal vaccine delivery

Abstract: Skin is an attractive but also very challenging immunisation site for particulate subunit vaccines. The aim of this study was to develop hyaluronan (HA)-based dissolving microneedles (MNs) loaded with PLGA nanoparticles (NPs) co-encapsulating ovalbumin (OVA) and poly(I:C) for intradermal immunisation. The NP:HA ratio used for the preparation of dissolving MNs appeared to be critical for the quality of MNs and their dissolution in ex vivo human skin. Asymmetrical flow field-flow fractionation and dynamic light … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(35 citation statements)
references
References 38 publications
0
33
0
Order By: Relevance
“…The antigen association in the shell of nanocapsules allows a fast recognition by immunocompetent cells and therefore it is expected that it would trigger an efficient immune response. Other nanoformulations have shown similar or lower OVA loading efficiency in comparison to our CSNCs [ 40 , 41 ].…”
Section: Resultsmentioning
confidence: 67%
“…The antigen association in the shell of nanocapsules allows a fast recognition by immunocompetent cells and therefore it is expected that it would trigger an efficient immune response. Other nanoformulations have shown similar or lower OVA loading efficiency in comparison to our CSNCs [ 40 , 41 ].…”
Section: Resultsmentioning
confidence: 67%
“…Particle based antigen carriers can also serve as a depot for controlled release of antigen, thereby increasing the availability of antigen to the immune cells [42,43]. In addition, particle-based adjuvants possess the ability to modulate the type of induced immune responses when used alone or in combination with other immune-stimulatory compounds [44]. Particulates can protect the integrity of antigens against degradation until delivered to the immune cells as antigens must be protected from the harsh acidic conditions of the stomach and enzymatic degradation in the GI tract [45,46].…”
Section: Particulate Vaccinesmentioning
confidence: 99%
“…Monkare et al have developed a PLGA nanoparticle-based microneedle for vaccine delivery [44]. The hyaluronan (HA)-based dissolving microneedles (MNs) are loaded with PLGA nanoparticles (NPs) co-encapsulating ovalbumin (OVA) and poly(I:C) for intradermal immunization.…”
Section: Particulate Vaccinesmentioning
confidence: 99%
See 1 more Smart Citation
“…Given to BALB/c mice, the multiple adjuvant-constituted PLGA NPs loaded with Ags induced robust and efficient immune responses, as confirmed by evaluation of vivo cytokine (IFN-γ, IL-4, and IL-1β) secretion and antibody (IgG1 and IgG2a) production, demonstrating using a combination of adjuvants in a context-dependent manner may a feasible strategy for engineering a potent PLGA-based VADS. To make subunit vaccines suitable for immunization via skin, which is an attractive but also very challenging immunization site due to the presence of affluent APCs while difficulty of administration, recently, Bouwstra's group fabricated the hyaluronan (HA)-based dissolving microneedles (MNs) entrapped with PLGA NPs which co-encapsulated ovalbumin (OVA) as an Ag and poly(I:C) as an adjuvant for intradermal immunization [56]. Further investigation indicated that the immunogenicity of the PLGA NPs after administration of dissolving MNs was compared with that of hollow MN-delivered PLGA NPs in mice, while immunization with free Ag in dissolving MNs resulted in equally strong immune responses compared to delivery by hollow MNs.…”
Section: Plga Npsmentioning
confidence: 99%